Trade policy and city primacy in developing countries - Gelan, Ayele (Wiley, 2008)
This paper examines the relationship between trade policy and city primacy in developing countries. A general equilibrium model was constructed and center-periphery relations are analyzed, accounting for tensions between agglomerative and distributive forces. By applying the theoretical model through numerical simulations, we analyzed how trade policy affects the interactions between these forces. We distinguished between import tariffs and export trade barriers. The results suggested that trade liberalization can reduce the dominance of mega-cities in developing countries, but only when improvements are made to internal and external factors inhibiting their export trade. These include improving domestic transport infrastructure and reducing barriers to exports from developing countries by developed nations.